Avaliação clínico epidemiológica de pacientes com melanoma uveal de duas instituições do estado de São Paulo e elaboração de protocolo de atendimento multidisciplinar no Hospital de Clínicas da Universidade Estadual de Campinas : Epidemiological and clinical assessment of patients with uveal melanoma from two institutions in the state of São Paulo and elaboration of multidisciplinary care protocol at the General Hospital of the University of Campinas - Vertuan, Andreza, 1988- (2021)
Orientador: Carmen Silvia Passos Lima